Effects of nitrate supplementation in trained and untrained muscle is modest with initial high plasma nitrite levels - Christensen, P. M.; Petersen, N. K.; Friis, S. N.; Weitzberg, E.; Nybo, L. (Scandinavian Journal of Medicine & Science in Sports, 2017)
Nitrate (NO3-) supplementation resulting in higher plasma nitrite (NO2-) is reported to lower resting mean arterial blood pressure (MAP) and oxygen uptake (VO2) during submaximal exercise in non-athletic populations, whereas effects in general are absent in endurance trained individuals. To test whether physiological effects of NO3- supplementation depend on local muscular training status or cardiovascular fitness, male endurance-trained cyclists (CYC, n=9, VO2-max: 64±3 ml/min/kg; mean±SD) and recreational active subjects serving as a control group (CON, n=8, 46±3 ml/min/kg), acutely consumed nitrate-rich beetroot-juice ([NO3-] ~9 mmol) (NIT) or placebo (PLA) with assessment of resting MAP and energy expenditure during moderate intensity (~50% VO2-max) and incremental leg cycling (LEG-ex) and arm cranking exercise (ARM-ex). NIT increased (P<0.001) resting plasma NO3- by ~1200% relative to PLA. Plasma NO2- increased ~25% (P<0.01) with a significant change only in CYC. LEG-ex VO2 (~2.60 L/min), ARM-ex VO2 (~1.14 L/min) and resting MAP (~87 mm Hg) remained unchanged for CYC and similarly for CON no changes were observed for LEG-ex VO2 (~2.03 L/min), ARM-ex VO2 (~1.06 L/min) or resting MAP (~85 mm Hg). VO2-max was not affected by supplementation but incremental test peak power was higher (P<0.05) in LEG-ex for CYC in NIT relative to PLA (418±47 vs. 407±46 W). In both CYC and CON high initial baseline values and small increases in plasma NO2- after NIT may have lowered the effect of the intervention implying that muscular and cardio-vascular training status is likely not the only factors that influence the physiologic effects of NO3- supplementation.